Analisis Ketidakseimbangan Beban Pada Tranformator Distribusi Di Gardu Induk Budurn - Wijayanto, Viky; Slamet, Puji; Widagdo, Reza Sarwo (Jurnal Teknik Informatika dan Elektro, 2023)
Electricity is a basic need for humans today, it has been proven that humans are very dependent on electricity for their daily activities. If electricity is not available, then human daily activities will be disrupted. The occurrence of load imbalance that occurs in the R, S, and T phases due to the absence of concurrent when the load is turned on, resulting in a neutral current flow on the secondary side of the transformer. with the development of electric power distribution systems. The benefit of reducing losses on the neutral conductor of the distribution transformer is that it can produce savings in the supply of electricity, and other benefits obtained include the resulting system. The method used is that the data resulting from field measurements are converted into mathematical equations. From the research conducted, the results showed the average value of the loading current and load imbalance in the distribution transformer at the Buduran Substation, namely the average loading current of (14.4 A), Load Imbalance of (28.3 A), Neutral Current Losses of (2.34 W). And Copper Losses of (0.510945 kW).